SHARI’AH TOURISM ISLAMIC BOARDING SCHOOL MODEL (Case Study of Salafiah Biharu Bahri Asali Fadlailir Rahmah Islamic Boarding School Malang) - Suwarno, Suwarno; Chasanah, Uswatun; Suradji, Muchamad; Harahap, Ahmad Yunus Mokoginta (Jurnal As-Salam, 2023)
Islamic boarding schools are educational institutions in Indonesia that have the characteristics of learning using classical literature. Islamic boarding school education in Indonesia had existed before independence, and until now, it still exists with various pesantren models. One of the highlights is the model of a tourist boarding school in Sananrejo Village, Turen District, Malang Regency, which has aroused the author’s interest in conducting this research. This research aims to describe the Islamic tourism boarding school model in the Salafiah Bihaaru Bahri Asali Fadlaailir Rahmah Islamic Boarding School. The research method used in this research is a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation and interviews. Then the data were analyzed using inductive qualitative data analysis through three stages simultaneously: reduction, data presentation, and conclusion. The results of the study revealed that the Bi Ba’a Fadlrah Islamic boarding school is a salaf Islamic boarding school that only teaches religious material and does not open formal schools. The material taught is more on Sufism so that students become individuals who are good at being grateful, sincere, pleased, and qana’ah. Sharia tourism activities are open every day with a full 24-hour duration. Every day visitors reach tens of thousands, and the quietest is around three thousand, coming from various regions. Visitors are not charged an entrance ticket. Inside the pesantren is a shopping area in the form of culinary and souvenirs at affordable prices.